Intranasal Cerium Oxide Nanoparticles Ameliorate Cognitive Function in Rats with Alzheimer's via Anti-Oxidative Pathway - Syed Mohammad Danish; Anshul Gupta; Urooj Ahmad Khan; Nazeer Hasan; Farhan Jalees Ahmad; Musarrat Husain Warsi; Ahmed M. Abdelhaleem Ali; Ameeduzzafar Zafar; Gaurav Kumar Jain (MDPI AG, 2022)
Cerium oxide nanoparticles (CNPs), owing to their antioxidant property, have recently emerged as therapeutic candidate for Alzheimer's disease (AD). However, intravenous CNPs are limited due to their poor physicochemical properties, rapid blood clearance and poor blood-brain penetration. Thus, we developed intranasal CNPs and evaluated its potential in experimental AD. CNPs were synthesized using homogenous precipitation method and optimized through Box-Behnken Design. The formation of CNPs was confirmed by UV spectroscopy and FTIR. The optimized CNP were spherical, small (134.0 ± 3.35 nm), uniform (PDI, 0.158 ± 0.0019) and stable (ZP, −21.8 ± 4.94 mV). The presence of Ce in CNPs was confirmed by energy-dispersive X-ray analysis. Further, the X-ray diffraction spectra revealed that the CNPs were nano-crystalline. The DPPH assay showed that at concentration of 50 µg/mL, the percentage radical scavenging was 95.40 ± 0.006%. Results of the in vivo behavioral studies in the scopolamine-induced Alzheimer rat model showed that intranasal CNPs dose dependently reversed cognitive ability. At dose of 6 mg/kg the morris water maze results (escape latency, path length and dwell time) and passive avoidance results (retention latency) were significantly different from untreated group but not significantly different from positive control group (rivastigmine patch, 13.3 mg/24 h). Further, biochemical estimation showed that intranasal CNP upregulated the levels of SOD and GSH in brain. In conclusion, intranasal CNPs, through its antioxidant effect, could be a prospective therapeutics for the treatment of cognitive impairment in AD.